2007
DOI: 10.1002/aic.11170
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic approach to enhancement of the yield of a sonochemical reaction

Abstract: in Wiley InterScience (www.interscience.wiley.com).In this study, a mechanistic approach has been taken to enhance yield of a sonochemical reaction. Formation of highly reactive free radicals due to the transient collapse of cavitation bubbles is the primary mechanism of a sonochemical reaction. A physical (reduction in dissolved gas concentration) and a chemical (increasing the reactant concentration) technique is used for enhancing yield of a sonochemical reaction using those techniques, which influence the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
78
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 132 publications
(80 citation statements)
references
References 46 publications
2
78
0
Order By: Relevance
“…Prior to the experiments, the sonication bath was characterized with calorimetric measurements for actual power dissipation and the distribution of acoustic pressure amplitude. 25,29 The ultrasound intensity (and, hence, the ultrasound pressure amplitude) in the bath shows significant spatial variation. To avoid the variation in the ultrasound pressure amplitude in different experiments (which could give rise to artifacts), the conical flask containing dye solution was placed at the center of the sonication bath, and its position was carefully maintained constant in all experiments.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior to the experiments, the sonication bath was characterized with calorimetric measurements for actual power dissipation and the distribution of acoustic pressure amplitude. 25,29 The ultrasound intensity (and, hence, the ultrasound pressure amplitude) in the bath shows significant spatial variation. To avoid the variation in the ultrasound pressure amplitude in different experiments (which could give rise to artifacts), the conical flask containing dye solution was placed at the center of the sonication bath, and its position was carefully maintained constant in all experiments.…”
Section: Methodsmentioning
confidence: 99%
“…The extent of production of radicals through cavitation bubbles depends on three factors 25 (1) the bubble population in the medium, (2) extent of evaporation of H 2 O 2 , which in turn depends on the concentration of H 2 O 2 in the solution and its partial pressure, and (3) peak temperature and pressure reached in the bubble at transient collapse, which in turn depends on frequency and pressure amplitude of the ultrasound wave. It should be noted that excess concentration of H 2 O 2 in the medium could have adverse effect on degradation/decolorization as the • OH radicals generated by either cavitation bubbles or Fenton reactions can get converted to molecular species due to scavenging action of H 2 O 2 through following reactions…”
Section: Contemplations and Conjecturesmentioning
confidence: 99%
“…A mechanistic approach to the enhancement of the yield of a sonochemical reaction showed that the collapse of cavitation bubbles and sonochemical yield is a complicated function of several interdependent physical processes such as rectified diffusion, water vapour transport, and entrapment in cavitation bubbles. Further, it was reported that the degassing of the reaction medium intensifies the collapse of the cavitation bubbles, resulting in higher production of OH and other radicals, which enhance the yield of the sonochemical reaction (Sivasankar et al 2007). Furthermore, higher oxidation of iodide to iodine was observed at a sonication frequency of 574 kHz compared to the other four frequencies 378, 860, 992, and 1173 kHz (Figs.…”
Section: Effect Of Sonication Frequencymentioning
confidence: 91%
“…The yield of KI oxidation reaction can be defined as the number of moles of iodine liberated per unit time per unit reaction volume per unit mole of KI per unit power input to the system (Sivasankar et al 2007). A decrease in cavitation yield as a result of decreasing KI concentration was observed for all types of sonication frequencies tested (Figs.…”
Section: Effect Of Power Supplied and Ki Concentrationmentioning
confidence: 95%
“…Transport of solvent vapor in the bubble during radial motion, and its entrapment in the bubble at the moment of transient collapse leads to formation of radicals through thermal dissociation of the vapor molecules. Greater details on this model can be found in our previous papers (Krishnan et al, 2006;Sivasankar et al, 2007), as well as in the original papers (Toegel et al, 2000;Toegel and Lohse, 2003). For the convenience of the readers, essential equations and thermodynamic data of this model have been given in Tables S.1 and S.2 in the supplementary material.…”
Section: Model For Cavitation Bubble Dynamicsmentioning
confidence: 99%